Título Padrão - Rocha, Valesca Paula; Silveira, Ilana de Oliveira; Cascon, Helena Matthews (Arquivos de Ciências do Mar, 2015)
TheSpondylidae is a bivalve family that includes big and notable members of the corals fauna, rarely occurring in estuarine areas. For the Brazilian coast, four species of the genus Spondylus have been reported. The absence of a well- researched and agreed-upon taxonomic list for bivalves often causes the most basic problems, like difficulty to determine the valid name for a taxon. A great variability within the same species, diagnoses based on the shell’s characteristics make its identification problematic. This study aims to do a brief discussion about identification and taxonomic problems of the family, as well as to show the variations of shell ornamentation in Spondylus species that occur in Northeast Brazil. To this end, a short review of the literature was carried out, and the Spondylidae shells deposited in the Prof. Henry Ramos Matthews Malacological Collection” (CMPHRM – Serie B), at the Universidade Federal do Ceará, were inspected. The family has a wide area yet to be explored and it is necessary to make a comprehensive review of this group. The Brazilian shells observed, as expected, showed a large variation on ornamentation.